Improving Reading Comprehension through Comic Strip for Ninth Grade - Ni'mah, Fauziyatun; Nur, Luluk Choirun Nisak; Mushthoza, Dina Amaliyah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research focuses in reading comprehension of narrative text by using comic strips for the ninth grade students. This research aims to describe the implementation of comic strips to improve the ninth grade students’ reading comprehension at MTs Miftahul Ulum Melirang. The result of this research shows that there are two cycles with two meetings in every cycle. In the first cycle, 12 students pass the passing grades with percentages 48%. Therefore, the first cycle is still low to become successful. In the second cycle, 84% or 21 total students achieves the passing grade. Moreover, most of the students in the second cycle pass the passing grade, so this research is categorized successful. It indicates that comic strip is the effective media to improve students reading comprehension for the ninth grade students of MTs Miftahul Ulum Melirang